2012
DOI: 10.4317/medoral.17469
|View full text |Cite
|
Sign up to set email alerts
|

Immediate implants following tooth extraction. A systematic review

Abstract: Objectives: The aim of this article is to review the current state of immediate implants, with their pros and contras, and the clinical indications and contraindications. Material and Methods: An exhaustive literature search has been carried out in the COCHRANE library and MEDLINE electronic databases from 2004 to November 2009. Randomized clinical trials and clinical trials focused on single implants placed in fresh extraction sockets were included and compared. A meta-analysis could not be performed due to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
77
0
5

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(87 citation statements)
references
References 27 publications
5
77
0
5
Order By: Relevance
“…Most papers contained only data on implant loss, but did not provide useful information on implant failure or hard and soft tissue changes. Their data match the results of the present review, in which most of the articles reported data on implant survival rates but not on implant success rates, according to the criteria described by Albrektsson et al 7 Depending on the degree of damage of the extraction socket and of the shape as well as the diameter of the extracted root, some portion of the implants could remain exposed and/or there might remain a residual gap between the implant and the bony wall. Since alveolar bone will remodel after tooth extraction, the degree of bone resorption is difficult to predict and could leave some portion of the implants exposed, determining a poor esthetic outcome.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Most papers contained only data on implant loss, but did not provide useful information on implant failure or hard and soft tissue changes. Their data match the results of the present review, in which most of the articles reported data on implant survival rates but not on implant success rates, according to the criteria described by Albrektsson et al 7 Depending on the degree of damage of the extraction socket and of the shape as well as the diameter of the extracted root, some portion of the implants could remain exposed and/or there might remain a residual gap between the implant and the bony wall. Since alveolar bone will remodel after tooth extraction, the degree of bone resorption is difficult to predict and could leave some portion of the implants exposed, determining a poor esthetic outcome.…”
Section: Discussionsupporting
confidence: 86%
“…6 Over time, clinical experience has provided the criteria for immediate implant treatment success: atraumatic tooth extraction, sterilization and minimal invasive surgical approach, as well as implant primary stability. 7 Quirynen et al focused their review on immediate vs delayed implant placement. Most papers contained only data on implant loss, but did not provide useful information on implant failure or hard and soft tissue changes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They as well as Ortega-Martínez et al clearly demand more studies evaluating the bone situation for the future [28]. This question was the motivation for our study.…”
Section: Discussionmentioning
confidence: 93%